Wireless physical-layer security model based on perturbation theory and sensitivity analysis - Hong-quan WEI; Wen-yu LUO; Ju-long LAN; Hong-chang CHEN (Tongxin xuebao)
Many typical models had been proposed for wireless physical-layer security, which have some disadvantages and limitations in theoretical analysis or implementation respectively. Considering these shortages brought about by the existing works, a physical-layer security model used in frequency selective fading channel based on perturbation theory was proposed. The proposed model finds a tradeoff between the availability and the security of the practical system by adjusting the threshold of perturbation. At last, the validity and feasibility are illustrated by the sensitivity analysis and application example.